Research on the Curriculum Reform of International Business Undergraduate Education in the Context of China's Fashion Industry (Journal of educational development exploration, 2026)
This study addresses the new demands for international business talents arising from the globalization transformation of China's fashion industry. It constructs a modular curriculum system guided by the core principles of "industry leadership, cross-border integration, and practice orientation." Through systematic design of four major curriculum modules and integration of international advanced educational experiences with local practical cases, the reform aims to cultivate versatile international business talents with global perspective, cultural intelligence, and innovative capabilities. This initiative provides talent support for Chinese fashion brands going global and promotes innovative development in international business undergraduate education.
Keywords: International business; Fashion industry; Curriculum reform